Urban professionals’ restorative tourism: exploring the role of perceived environmental restorativeness, push and pull motivations and destination attributes on tourism expectations - Ding, Xianyao; Xu, Jiajun (Frontiers in Psychology, 2024)
Urban professionals often seek respite from their daily routines through restorative tourism, driven by a complex interplay of motivations that include both internal "push" factors and external "pull" factors. This study investigates the intricate relationship between the perceived environmental restorativeness of tourist destinations and the expectations of urban professionals engaging in restorative tourism. Furthermore, it examines how push and pull motivations mediate this relationship while also considering the moderating effect of destination attributes. The multiple regression analyses on the survey data collected from 221 urban professionals with restorative tourism experiences provided quantitative evidence regarding the hypothesized relationships among perceived environmental restorativeness, push and pull motivations, destination attributes, and tourism expectations. The results showed that perceived environmental restorativeness has a positive effect on urban professionals' tourism expectations; urban professionals' pull motivation and push motivation each play a mediating role between perceived environmental restorativeness and tourist expectations; and restorative tourism destination attributes have a moderating effect between perceived environmental restorativeness and push motivation, as well as the relationship between perceived environmental restorativeness and pull motivation. This study provides essential theoretical contributions to restorative tourism and practical implications when designing restorative tourism destinations that target urban professionals.